Penggaruh Permainan Tradisional Tarik Tambang Terhadap Perkembangan Sosial Anak Usia 5-6 Tahun di Tk Panca Budi Medan - Siti Mahyuni Harahap (Jurnal Mutiara Pendidikan Indonesia, 2019)
In this study the problem is the lack of social development of children aged 5-6 years. This study aims to determine the effect of the traditional game of tug of war on the social development of children aged 5-6 years in kindergarten Panca Budi T.A. 2019/2020. This research is a quantitative (experimental) research, namely Pre-Experimental Designs in the form of One-Group Pretest-posttest design. The study population was children in class B2 Kindergarten Panca Budi Medan. This research was conducted using a sample of 11 children, namely before the treatment is done once a week done in two weeks and after the treatment is done twice a week carried out in two weeks with a game of tug of war. Based on the analysis results obtained an average value before treatment 7.27 with the highest value of 10 and the lowest 4 then after treatment an average value of 9.63 with the highest value of 11 and the lowest of 8. Thus it can be concluded that learning using the traditional game of tug of war can affect the social development of children aged 5-6 years in kindergarten Panca Budi Medan T.A. 2019/2020.